Analysis of The Applications of Payroll and Wage Accounting Systems in Supporting Internal Control (Case Study at TK Aisyiyah Bustanul Athfal) - Putri Sepiyana; Hotbin Hasugian; Laylan Syafina (Quantitative Economics and Management Studies, 2024)
This research focused on an in-depth analysis of the implementation of payroll accounting and wage system in TK Aisyiyah Bustanul Athfal and its impact on school internal control. Using descriptive approaches and qualitative methodologies, data were collected through various techniques such as documentation, observation, and interviews. The findings of this study show that although the payroll and wage systems implemented have proven relatively effective, there are still significant shortcomings regarding administrative tasks, the use of documents, and accounting records. The implications of this study highlight the urgency to continuously improve the payroll accounting system to strengthen internal control at TK Aisyiyah Bustanul Athfal. These corrective measures should prioritize optimizing administrative processes and maintaining more accurate and detailed accounting records, thereby ensuring compliance with applicable internal control standards. The study provides valuable insights into the development of financial and human resource management strategies in an educational environment.